Microwave-Assisted Atom Transfer Radical Cyclization in the Synthesis of 3,3-Dichloro-γ- and δ-Lactams from N-Alkenyl-Tethered Trichloroacetamides Catalyzed by RuCl2(PPh3)3 and Their Cytotoxic Evaluation - Faïza Diaba; Alexandra G. Sandor; María del Carmen Morán (Molecules, 2024)
An expeditious synthesis of γ- and δ-lactams from tethered alkenyl trichloroacetamides in the presence of 5% of RuCl2(PPh3)3 is reported. In this investigation we have demonstrated that microwave activation significantly enhances reaction rates, leading to the formation of the corresponding lactams in yields ranging from good to excellent. Thus, we have been able to prepare a wide range of lactams, including indole and morphan bicyclic scaffolds, where the corresponding reactions were completely diastereoselective. This process was successfully extended to α,α-dichloroamides without affecting either their yield or their diastereoselectivity. Some of the lactams prepared in this work were evaluated for their hemolytic and cytotoxic responses. All compounds were found to be non-hemolytic at the tested concentration, indicating their safety profile in terms of blood cell integrity. Meanwhile, they exhibited interesting cytotoxicity responses that depend on both their lactam structure and cell line. Among the molecules tested, γ-lactam 2a exhibited the lowest IC50 values (100–250 µg/mL) as a function of its cell line, with promising selectivity against squamous carcinoma cells (A431) in comparison with fibroblasts (3T3 cell line).